Global Status of Emerging Lophomonas Infection: A Systematic Review of Reported Cases (1993—2020) - Maryam Nakhaei; Mahdi Fakhar; Ali Sharifpour; Hajar Ziaei Hezarjaribi; Elham Sadat Banimostafavi; Eisa Nazar (Interdisciplinary Perspectives on Infectious Diseases)
Purpose. Lophomonas spp., is an emerging protozoan parasite that belongs to the Parabasalids (Parabasalia, lophomonadida) which infects the respiratory tracts of humans. Despite the presence of a few reports of human lophomoniasis, the true burden of Lophomonas infection is unknown. This systematic review aimed to elucidate the latest global status of publications reporting human cases of lophomoniasis as a new emerging protozoal disease. Methods. A comprehensive and systematic search was performed in 10 (five English and five Persian) databases for studies reporting cases of lophomoniasis between 1993 and March 2020 (27 years). Then, the selected articles were carefully reviewed and screened based on the inclusion and exclusion criteria. Results. Overall, 32 eligible publications reporting 307 lophomoniasis cases from around the world are included in this review. The patients were aged between 1 month and 84 (mean age = 23.7 years). The highest number of cases (n = 171; 55.7%, P<0.04) significantly belonged to the juvenile age group (aged ≤18 years). The male to female ratio of the cases was almost equal, and no statistically significant difference between them was observed. The maximum number of cases (n = 237) was reported from Iran. Most cases (n = 196; 63.85%) had no history of underlying diseases/organ transplantation P<0.001. Moreover, the BAL specimen was the most commonly used clinical sample to diagnose lophomoniasis P<0.001. Conclusion. Our findings reveal that the prevalence of lophomoniasis is likely to be markedly underestimated when evaluated based on published case reports. Additionally, our data, at least for the time being, supports the idea that Lophomonas spp. should not be considered as an opportunistic infection. Thus, current work sheds light on some controversial issues regarding the epidemiological aspects of lophomoniasis.